Concrete composition
A concrete composition using blast furnace slag fine powder optimally replaces Portland cement and aggregates to enhance strength and reduce costs and emissions, addressing the challenges of existing technologies.
Patent Information
- Application Number
- JP2023118812
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-31
AI Technical Summary
Existing concrete compositions that replace part of Portland cement with blast furnace slag fine powder (GGBF) face issues of increased costs and delayed initial and medium-term strength due to the need for special additives and manufacturing processes.
A concrete composition that replaces 30 to 50% of cement with blast furnace slag fine powder (GGBF) and 15 to 45% of fine aggregates with blast furnace slag fine powder, using a simple method without special additives or dedicated manufacturing processes, optimizing the replacement rates to enhance initial and medium-term strength.
The composition effectively improves initial and medium-term strength of concrete while reducing costs and environmental emissions, utilizing recycled materials to conserve natural resources and reduce CO2 emissions during cement manufacturing.
Smart Images

Figure 2025015916000002 
Figure 2025015916000003 
Figure 2025015916000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a concrete composition used mainly in the fields of civil engineering and construction, and in particular to a concrete composition in which a part of ordinary Portland cement is replaced with ground granulated blast furnace slag. [Background technology]
[0002] There is a type of blast furnace cement in which ordinary Portland cement is partially replaced with GGBF, taking advantage of the latent hydraulic properties of granulated blast furnace slag powder (hereinafter referred to as GGBF). Generally, the type of blast furnace cement that is widely distributed is Type B blast furnace cement (JIS R5211), which has a replacement ratio of more than 30% and less than 60%, but GGBF is also sometimes mixed into ordinary Portland cement. It is said that using GGBF in concrete can improve workability, suppress heat of hydration, and improve chemical resistance, seawater resistance, and watertightness. Guidelines for use are provided in the "Design and Construction Guidelines for Concrete Using Ground Granulated Blast Furnace Slag." On the other hand, it is known that when part of ordinary Portland cement is replaced with GGBF, there is an issue that the early and medium-term strength development is delayed as the replacement rate increases.
[0003] Methods for improving the early and medium-term strength of concrete using GGBF are disclosed in, for example, Patent Documents 1 and 2. Patent Document 1 describes that the early and mid-term strength of concrete using GGBF is improved by (i) mixing cooled blast furnace slag aggregate as part or all of the fine aggregate and / or coarse aggregate, (ii) adding one or more stimulants selected from portland cement, limestone, calcium hydroxide, and an expansion agent, and (iii) adding one or more admixtures selected from fine limestone powder, fly ash, and silica foam. Furthermore, Patent Document 2 describes that for concrete containing a large amount of GGBF, the early to mid-term strength development can be improved by adding a dedicated additive composition during the manufacturing process of GGBF for cement. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-145033 A [Patent Document 2] Patent Application No. 2016-199452 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the techniques described in Patent Documents 1 and 2 require the addition of special additives or multiple additives, special mixes, and dedicated manufacturing processes and plants. Therefore, although the early and medium-term strength of concrete using GGBF can be improved, there are issues such as the complexity of the manufacturing process and manufacturing means and increased costs. Therefore, the object of the present invention is to solve the above-mentioned problems of the conventional technology and to provide a concrete composition that effectively improves the early and medium-term strength of concrete using GGBF at low cost and in a simple manner without using special additives or dedicated manufacturing processes or plants. [Means for solving the problem]
[0006] The present invention was developed through various mixing tests to solve the above problems, and has improved the delay in early and mid-term strength development of concrete in which part of ordinary Portland cement has been replaced with GGBF, using a low-cost and simple method. The features of the method are as follows: [1] A concrete composition in which the binder is ordinary Portland cement and the fine aggregate is sand, and the unit binder weight is 340 to 370 kg / m 3, water-binder ratio is 48-52%, and unit coarse aggregate amount is 900-1100kg / m 3 , for concrete compositions with fine aggregate ratios of 42-48%, A concrete composition characterized in that 30 to 50% of the cement mass ratio is replaced with ground granulated blast furnace slag slag, and 15 to 45% of the fine aggregate volume ratio is replaced with granulated blast furnace slag fine aggregate.
[0007] [2] In the concrete composition according to [1] above, the ground granulated blast furnace slag has a fineness of 4000 as specified in JIS A6206:2013 and contains 4 mass% or less of gypsum. [3] The concrete composition according to the above [1] or [2], wherein the coarse particle ratio of the granulated blast furnace slag fine aggregate is 2.35 to 2.75. [4] The concrete composition according to the above [1] or [2], characterized in that the concrete composition contains an admixture mainly composed of a complex of a lignin sulfonate compound and a polycarboxylate ether in an amount of 1.2 to 1.5 mass % per unit binder weight. [5] A concrete floor, characterized in that the concrete is made of a hardened concrete composition of any one of the above [1] to [4]. Effect of the Invention
[0008] According to the present invention, the early and medium-term strength of concrete in which part of the cement has been replaced with ground granulated blast-furnace slag can be effectively improved by a low-cost and simple method of replacing part of the fine aggregate with granulated blast-furnace slag fine aggregate, without using special additives or dedicated manufacturing processes or plants, etc. Furthermore, by optimizing the replacement rate of the ground granulated blast-furnace slag, there is also the advantage that the early strength development can be accelerated and higher strength can be achieved than in ordinary concrete. In addition, because granulated blast furnace slag powder and granulated blast furnace slag fine aggregate are used as part of the materials, CO2 emissions from cement production are reduced. 2 This not only reduces emissions, but also helps prevent the depletion of natural resources by using recycled blast furnace slag. For these reasons, it can be said to be an environmentally friendly concrete. [Brief description of the drawings]
[0009] [Figure 1] A graph showing the compressive strength of concrete G50B0, which is made by replacing part of the cement in ordinary concrete G0B0 with GGBF, at 7 days, along with the compressive strength of ordinary concrete G0B0 at 7 days. [Diagram 2] A graph showing the 28-day compressive strength of concrete G50B0, in which part of the cement in ordinary concrete G0B0 has been replaced with GGBF, along with the 28-day compressive strength of ordinary concrete G0B0. [Diagram 3] A graph showing the 7-day compressive strength of concrete G0B30 and concrete G0B50, in which part of the fine aggregate in ordinary concrete G0B0 has been replaced with BFS, along with the 7-day compressive strength of ordinary concrete G0B0. [Figure 4] A graph showing the 28-day compressive strength of concrete G0B30 and concrete G0B50, in which part of the fine aggregate in ordinary concrete G0B0 has been replaced with BFS, along with the 28-day compressive strength of ordinary concrete G0B0. [Diagram 5] A graph showing the 7-day compressive strength of concrete G30B30, concrete G50B30, concrete G50B50, and concrete G50B100, in which part of the cement in ordinary concrete G0B0 has been replaced with GGBF and part or all of the fine aggregate has been replaced with BFS, together with the 7-day compressive strength of ordinary concrete G0B0 and concrete G50B0. [Figure 6] A graph showing the 28-day compressive strength of concrete G30B30, concrete G50B30, concrete G50B50, and concrete G50B100, in which part of the cement in ordinary concrete G0B0 has been replaced with GGBF and part or all of the fine aggregate has been replaced with BFS, together with the 28-day compressive strength of ordinary concrete G0B0 and concrete G50B0. [Figure 7] A graph showing the relationship between the BFS replacement rate and the 28-day compressive strength for ordinary concrete G0B0 in which part of the cement has been replaced with GGBF. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In the following explanation, granulated blast furnace slag powder is called GGBF and granulated blast furnace slag fine aggregate is called BFS. Concrete that uses only ordinary Portland cement as a binder and only sand (land sand) as a fine aggregate is called "ordinary concrete G0B0" (G0B0 means 0% replacement rate of GGBF by mass and 0% replacement rate of BFS by volume). On the other hand, concrete that replaces △△% of ordinary Portland cement with GGBF and ▲▲% of fine aggregate sand (land sand) by volume with BFS is called "concrete G△△B▲▲". For example, concrete that replaces 50% of ordinary Portland cement with GGBF by mass and 30% of fine aggregate sand (land sand) by volume with BFS is called "concrete G50B30". Similarly, concrete made by replacing 50% by mass of ordinary Portland cement with GGBF and not replacing the fine aggregate sand (land sand) with BFS is called "concrete G50B0." Similarly, concrete made by not replacing ordinary Portland cement with GGBF and replacing 50% by volume of the fine aggregate sand (land sand) with BFS is called "concrete G0B50."
[0011] The concrete composition of the present invention is a concrete in which a part of the cement and fine aggregate of a specific base composition of ordinary concrete G0B0 is replaced with GGBF and BFS. The base composition of the concrete composition of the present invention is a concrete in which the binder is ordinary Portland cement and the fine aggregate is sand, and the unit binder amount is 340 to 370 kg / m 3 , water-binder ratio is 48-52%, and unit coarse aggregate amount is 900-1100kg / m 3 , the fine aggregate ratio is 42-48%. The above water-to-binder ratio is for a nominal strength of 30N / mm 2The water-binder ratio is calculated so that the range of adjustment for test mixing is about ±5%, with reference to the "Mix Design and Construction Guidelines and Commentary for Concrete Using Blast Furnace Slag Fine Aggregate." Additionally, the unit binder volume, unit coarse aggregate volume, and fine aggregate rate are also specified accordingly, with a range set according to the water-binder ratio.
[0012] Ordinary concrete G0B0 and concretes with various replacement rates of GGBF and BFS were prepared. The mix proportions of these concretes are shown in Table 1. For each concrete, ordinary Portland cement was used as the binder other than GGBF, land sand was used as the fine aggregate other than BFS, and limestone was used as the coarse aggregate. In addition, an AE water-reducing agent whose main component is a complex of lignin sulfonate compound and polycarboxylate ether was used as an admixture. The compressive strength of these concretes at 7 days (shown as "7-day strength" in Figures 1, 3, and 5) and at 28 days (shown as "28-day strength" in Figures 2, 4, and 6) was measured using a method conforming to JIS A1108. The results are shown in Figures 1 to 6. As shown in each figure, the compressive strength of concrete G0B0 at 7 days was 34.2 N / mm 2 The compressive strength at 28 days was 43.0N / mm 2 The compressive strengths shown in Figs. 1 to 6 are average values of N=3 measured values, and the variation in the measured values is shown in each graph.
[0013] [Table 1]
[0014] The compressive strength of concrete G50B0, in which 50% of the cement mass ratio of ordinary concrete G0B0 is replaced with GGBF (hereinafter, this replacement rate will be referred to as the "GGBF replacement rate"), is shown in Figures 1 and 2 along with the compressive strength of ordinary concrete G0B0. According to this, the compressive strength of concrete G50B0 at 7 days is lower than that of ordinary concrete G0B0 at 7 days. Also, the compressive strength of concrete G50B0 increases at 28 days, but it is still not equal to that of ordinary concrete G0B0.
[0015] The compressive strength of concrete G0B30, in which 30% of the volume ratio of the fine aggregate of ordinary concrete G0B0 is replaced with BFS (hereinafter, this replacement rate will be referred to as the "BFS replacement rate"), and concrete G0B50, in which 50% of the volume ratio of the fine aggregate is replaced with BFS, are shown in Figures 3 and 4, along with the compressive strength of ordinary concrete G0B0. According to this, the 7-day compressive strength of concrete G0B30, which has a 30% BFS replacement rate, is lower than that of ordinary concrete G0B0. On the other hand, the 7-day compressive strength of concrete G0B50, which has a 50% BFS replacement rate, is higher than that of ordinary concrete G0B0. From this, it can be said that in mixes where only BFS is substituted, the higher the BFS replacement rate, the higher the initial strength tends to be. Furthermore, in terms of 28-day compressive strength, both concrete G0B30 and concrete G0B50 show strength equal to or greater than that of ordinary concrete G0B0.
[0016] The compressive strength of concrete G30B30, in which the replacement rates of GGBF and BFS for ordinary concrete G0B0 are 30%, concrete G50B30, in which the replacement rate of GGBF is 50% and the replacement rate of BFS is 30%, concrete G50B50, in which the replacement rate of GGBF is 50% and the replacement rate of BFS is 50%, and concrete G50B100, in which the replacement rate of GGBF is 50% and the replacement rate of BFS is 100%, are shown in Figures 5 and 6, along with the compressive strength of ordinary concrete G0B0 and concrete G50B0.
[0017] According to this, all four mixes in which GGBF and BFS were substituted in combination had compressive strengths equal to or greater than that of concrete G50B0, which was substituted only with GGBF. In other words, it was found that the use of GGBF and BFS in combination can improve the delay in the development of early and mid-term strength, which is an issue with concrete that uses GGBF. The order of strength increase rate compared to concrete G50B0 is concrete G30B30, concrete G50G30, concrete G50B50, and concrete G50B100, and the smaller the BFS substitution rate, the greater the strength developed. This is a trend in contrast to the mixes in which only BFS was substituted as mentioned above, and is considered to be a characteristic of mixes in which GGBF and BFS were used in combination. In addition, concrete G30B30, which had a substitution rate of 30% GGBF and 30% BFS, not only suppressed the delay in the development of compressive strength at 7 days, but also showed a strength that exceeded the compressive strength of ordinary concrete G0B0 at 7 days. Regarding compressive strength at 28 days, the two mixes, concrete G30B30 and concrete G50B30, showed strength exceeding that of ordinary concrete G0B0.
[0018] From the above results, it was found that in order to improve the early and medium-term strength of concrete using GGBF, it is necessary to set the replacement rate of BFS within a specified range centered on 30% when the replacement rate of GGBF is 30-50%. Of the concretes shown in Table 1, the relationship between the BFS replacement rate and the 28-day compressive strength was analyzed using the concretes excluding ordinary concrete B0G0, concrete with a 0% GGBF replacement rate, and concrete G50B100 (which was excluded because of its poor fluidity, even though it has high strength). The results are shown in Figure 7. The approximate formula (y = -0.0105x 2 +0.6346x+35.942) is the compressive strength of normal concrete B0G0 at 28 days (43.0N / mm 2 The range of replacement rates for BFS exceeding 15% was calculated to be 15% to 45%.
[0019] Therefore, in the present invention, a concrete composition is obtained by replacing 30-50% of the cement mass ratio with GGBF (granulated blast furnace slag fine powder) and 15-45% of the fine aggregate volume ratio with BFS (granulated blast furnace slag fine aggregate) in the above-mentioned base concrete composition. This makes it possible to effectively improve the early and medium-term strength of concrete using GGBF. Furthermore, by setting the GGBF replacement rate at 30-50%, it is possible to achieve high strength by speeding up the development of early and medium-term strength compared to ordinary concrete. In addition, by using GGBF and BFS in combination, it is possible to reduce the CO2 emissions involved in cement production. 2 This not only reduces CO2 emissions, but also helps prevent the depletion of natural resources by using recycled blast furnace slag, making this an environmentally friendly concrete.
[0020] Preferred conditions for the concrete composition of the present invention will now be described. The concrete composition of the present invention usually contains an admixture. There are no particular limitations on the type or amount of the admixture, but it is particularly preferable to contain 1.2 to 1.5 mass% of an admixture containing a complex of a lignin sulfonate compound and a polycarboxylate ether (AE water reducing agent) as the main component, based on the unit binder amount. This admixture is an air entraining water reducer, and since the use of GGBF requires improving the workability of fresh concrete, it has two aims: to obtain the effects of the air entraining agent, and to reduce the unit water content as a water reducer, thereby suppressing bleeding. If the amount of AE water-reducing agent added is too small, it will be ineffective, and if it is too large, it will be costly. Therefore, experiments have shown that the fresh properties of concrete are stable and costs can be kept down, so it is preferable to add 1.2 to 1.5 mass% of the unit binder amount. An example of the AE water reducing agent, a complex of a lignin sulfonate compound and a polycarboxylate ether, is a product available from Pozzolith Solutions Co., Ltd. under the trade name "Master Polyhed 15S" (AE water reducing agent standard type (Type I), density: 1.01 to 1.13 g / cm 3 , total alkali content: 1.4%, chloride ion content: 0.00%).
[0021] The GGBF to be mixed into the concrete composition preferably has a fineness of 4000 as specified by JIS A6206:2013. In concrete in which part of the cement is replaced with GGBF, the greater the fineness of the GGBF (3000, 4000, 6000, 8000), the greater the compressive strength, especially the initial strength, but on the other hand, the greater the heat of hydration, which is a cause of cracking. In the present invention, the fineness is preferably 4000, with the aim of ensuring strength while suppressing the increase in heat of hydration. In addition, the fineness of 4000 is the fineness of GGBF that is commonly distributed, and ease of use was also taken into consideration.
[0022] Furthermore, GGBF can contain gypsum in an amount of 4% by mass or less. This is the range of content stipulated in JIS A6206:2013. The more gypsum is added, the more the heat of hydration is reduced, but the long-term strength tends to be smaller. However, an addition amount of about 2 to 4% by mass does not have a significant effect on the long-term strength. In the present invention, gypsum is added to suppress cracks for floors, but the amount added is preferably 4% by mass or less, which does not affect the long-term strength. In addition, the BFS preferably has a coarse grain ratio of 2.35 to 2.75. This is in accordance with JIS A1108, and specifies a range of ±0.20 for the coarse grain ratio of 2.55 determined through discussion between the manufacturer and the purchaser. The BFS coarse grain ratio of 2.55 was determined so as to include the coarse grain ratio of the land sand used, 2.62, within ±0.20.
[0023] The hardened concrete composition of the present invention can be applied to various civil engineering and architectural structures, but is particularly suitable for concrete floors of logistics warehouses, etc. The concrete composition of the present invention contains BFS as a part of the fine aggregate, so that the drying shrinkage of concrete can be suppressed, and thus the occurrence of cracks on the concrete surface can be suppressed. Concrete floors of logistics warehouses, etc. are subject to a large load from heavy objects, so that cracks are likely to occur on the surface, but by using the concrete composition of the present invention, the occurrence of such cracks can be suppressed, and it becomes possible to reduce the cost of repairing the cracks. In addition, by replacing part of the cement with GGBF, the CO generated during cement production can be reduced. 2 Toward the realization of a carbon-neutral society in 2050, the civil engineering and construction industries are also working to reduce CO emissions. 2 As a result of efforts to reduce carbon emissions, demand for low-carbon concrete is on the rise. In addition, if the early and mid-term strength delay of concrete using GGBF can be resolved, it is expected that construction time will be shortened.
Claims
1. A concrete composition in which the binder is ordinary Portland cement and the fine aggregate is sand, and the unit binder amount is 340 to 370 kg / m 3 , water-binder ratio is 48-52%, and unit coarse aggregate amount is 900-1100 kg / m 3 , for a concrete composition having a fine aggregate ratio of 42 to 48%, A concrete composition comprising: a cement mass ratio of 30 to 50% replaced with ground granulated blast furnace slag; and a fine aggregate volume ratio of 15 to 45% replaced with granulated blast furnace slag fine aggregate.
2. The concrete composition according to claim 1, characterized in that the ground granulated blast furnace slag has a fineness of 4000 as specified in JIS A6206:2013 and contains 4 mass% or less of gypsum.
3. 3. The concrete composition according to claim 1, wherein the coarse particle ratio of the granulated blast furnace slag fine aggregate is 2.35 to 2.
75.
4. 3. The concrete composition according to claim 1, further comprising an admixture having as its main component a complex of a lignin sulfonate compound and a polycarboxylate ether in an amount of 1.2 to 1.5 mass % per unit binder.
5. A concrete floor comprising a hardened concrete composition according to claim 1.
Citation Information
Patent Citations
Blast furnace slag fine particle composition and cement composition containing the blast furnace slag fine particle composition
JP2016199452A
Environment-conscious concrete composition
JP2018145033A